Synthesis and Function of Complex Sphingolipid Glycosylation. (June 2020) - Mortimer, Jenny C.; Scheller, Henrik Vibe
Abstract : Glycosylinositol phosphorylceramides (GIPCs) constitute an important class of plasma-membrane lipids in plants. The complex glycan headgroups of GIPCs vary between plant species and tissues. Recent studies have shown that the structure of the glycan headgroup is important for plant development, abiotic stress tolerance, and interactions with pathogenic and symbiotic microorganisms.